ON THE OCCURRENCE OF TRYPNOSOMES FROM CERTAIN HILL-STREAM FISHES OF ALMORA AND RELATED ALTERATIONS IN SOME BLOOD VALUES OF A FISH NEMACHEILUS RUPLICOLA (HORA) - JOSHL, B. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Survey was made in and around Almora, to find out the presence of any haemoflagellate parasite in fishes, during the year 1982-85. Out of 546 fishes, 21 specimens of 4 species viz. Puntius ticto (3), Channa gachua (4), Nemacheilus rupicola (12) and Garra gotyla (2) were found harbouring the trypanosomes. Studies made on the blood of 10 specimens of the Nemachilus showed that certain blood values undergo conspicuous changes due to the presence of this parasite.